EFEKTIVITAS POSYANDU LANSIA DALAM DETEKSI DINI PENYAKIT DEGENERATIF DI POSYANDU LANSIA DUSUN BANGSRI KARANGPANDAN - Rosita, Siskana Dewi; Mahmudah, Mutik (Jurnal Ilmiah Maternal, 2025)
The number of elderly people in Indonesia continues to increase, reflecting a major challenge in healthcare, particularly in addressing degenerative diseases such as hypertension, stroke, and diabetes mellitus. These conditions often develop without clear early symptoms, making early detection a crucial strategy to improve the quality of life for older adults. The Posyandu Lansia (Elderly Integrated Health Service Post), as a community-based healthcare service, has the potential to play a key role in the early detection of degenerative diseases. The aim of this study was to determine the effectiveness of Posyandu Lansia activities in improving early detection capabilities for degenerative diseases among the elderly in Bangsri Hamlet, Karangpandan. This research employed a quasi-experimental design with a one-group pre-test and post-test approach. The sample consisted of 40 elderly individuals actively participating in Posyandu activities, selected through purposive sampling. The intervention was in the form of health education regarding degenerative diseases. Data were collected using a questionnaire that had been tested for validity and reliability. Analysis was conducted using the paired t-test. The results showed that before the intervention, the majority of respondents (50%) had poor early detection skills. After the intervention, a significant improvement was observed, with 65% of respondents demonstrating good skills. The average early detection score increased from 58.25 to 73.40 (p = 0.000). The study concludes that Posyandu Lansia is effective in improving the knowledge and skills of elderly individuals in detecting the early symptoms of degenerative diseases. Community-based educational strategies, implemented in a simple yet structured manner, can have a significant impact on improving the health quality of older adults. Continuous support from healthcare workers, community cadres, and families is necessary to maintain program effectiveness